LOW INTEREST OF ACCOUNTING STUDENTS IN A CAREER AS AUDITOR - Maimunah, Mutiara (Catholic University Musi Charitas, 2024)
In this research, students' interests are focused on a career as an auditor. Several factors that can influence interest include financial rewards, work environment, and gender. The population in this study were students majoring in accounting at Palembang City University who were interested in a career as auditors. The sampling technique used was non-probability sampling with purposive sampling technique. The results of this research show that financial rewards are still the main goal of students in pursuing a career as an auditor or other profession. Meanwhile, the work environment does not influence students' interest in a career as an auditor. Meanwhile, gender has an influence on student interest because a high level of accuracy is needed in the auditor profession, so this also makes students choose a career as auditors.